[40]π Fused and Nonfused Core‐Modified Nonaphyrins: Syntheses and Structural Diversity. Issue 32 (6th July 2016) - Ghosh, Arindam; Srinivasan, A.; Suresh, Cherumuttathu H.; Chandrashekar, Tavarekere K.
Abstract: The synthesis of fused and nonfused core‐modified 40π nonaphyrins are reported. Spectroscopic and X‐ray structural studies reveal a twisted figure‐eight conformation in the freebase form that is nonaromatic. Structural changes occur, from figure‐eight to open extended conformation, upon protonation, thereby adopting 4nπ Hückel antiaromatic character, which is reflected in spectroscopic and theoretical studies. Such a structural change also induces ring inversions of specific heterocyclic rings by 180°. Abstract : Pieces of eight : Two 40π fused and nonfused core‐modified nonaphyrins, which exhibit figure‐eight conformations in the freebase form, are described. Protonation induces a structural change and thus leads to an open conformation with inversion of heterocyclic rings. Further protonation promotes nonaromatic character in the freebase form into Hückel 4nπ antiaromatic character.